Tumor suppression and apoptosis of human prostate carcinoma mediated by a genetic locus within human chromosome 10pter-q11. - Sanchez, Y (1996)
Prostate cancer is the second leading cause of male cancer deaths in the United States. Yet, despite a large international effort, little is known about the molecular mechanisms that underlie this devastating disease. Prostate secretory epithelial cells and androgen-dependent prostate carcinomas undergo apoptosis in response to androgen deprivation and, furthermore, most prostate carcinomas become androgen independent and refractory to further therapeutic manipulations during disease progression. Definition of the genetic events that trigger apoptosis in the prostate could provide important insights into critical pathways in normal development as well as elucidate the perturbations of those key pathways in neoplastic transformation. We report the functional definition of a novel genetic locus within human chromosome 10pter-q11 that mediates both in vivo tumor suppression and in vitro apoptosis of prostatic adenocarcinoma cells. A defined fragment of human chromosome 10 was transferred via microcell fusion into a prostate adenocarcinoma cell line. Microcell hybrids containing only the region 10pter-q11 were suppressed for tumorigenicity following injection of microcell hybrids into nude mice. Furthermore, the complemented hybrids undergo programmed cell death in vitro via a mechanism that does not require nuclear localization of p53. These data functionally define a novel genetic locus, designated PAC1, for prostate adenocarcinoma 1, involved in tumor suppression of human prostate carcinoma and furthermore strongly suggest that the cell death pathway can be functionally restored in prostatic adenocarcinoma.